Shortening Estimate and Structural Styles Interpretation In the Zagros Belt-Northeast of Iraq - Ali Mousa; Ahmed Hasan (Physical Sciences, Life Science and Engineering, 2025)
This study emphasizes how crucial it is to combine kinematic modeling, structural restoration, and seismic interpretation in order to comprehend the tectonic evolution of the Zagros FTB. The results shed light on the migration and storage of hydrocarbons, highlighting the impact of different stress regimes and deep-seated underlying structures on the petroleum systems in the area. We present the first regionally balanced reconstructed cross-section of the Zagros fold belt in northeastern Iraq, along with a two-dimensional kinematic model that shows how the belt has changed over time in the study area. Multiple Lower Triassic detachments are identified, detached above the ductile basement level, and intermediate detachments that may have caused internal complexities such as adaptive bending and/or asymmetric folding, and it suggests that the cross-section may have produced low-angle bends at the transition from brittleness to ductility, associated with the two main structural phases of the detachment level in the high and low fold zones. Different stratigraphic units exhibit differing degrees of shortening, according to balanced cross-section analysis; the Oligocene and Eocene units have the greatest shortening (8.14%). Multi-detachment folds, thrust propagation, and a heterogeneous strain distribution are characteristics of the deformation that are associated with uplift and regional compression in the basement. Hydrocarbon entrapment is significantly influenced by key structural features like the Kalar-Kirkuk Thrust (KKT), whereas exploration possibilities are impacted by differential erosion and subsidence.